Sequential Processing Enables 17% All-Polymer Solar Cells via Non-Halogen Organic Solvent - Chaoyue Zhao; Lihong Wang; Guoping Zhang; Yajie Wang; Ruiyu Hu; Hui Huang; Mingxia Qiu; Shunpu Li; Guangye Zhang (Molecules, 2022)
All-polymer solar cells (All-PSCs), whose electron donor and acceptors are both polymeric materials, have attracted great research attention in the past few years. However, most all-PSC devices with top-of-the-line efficiencies are processed from chloroform. In this work, we apply the sequential processing (SqP) method to fabricate All-PSCs from an aromatic hydrocarbon solvent, toluene, and obtain efficiencies up to 17.0%. By conducting a series of characterizations on our films and devices, we demonstrate that the preparation of SqP devices using toluene can effectively reduce carrier recombination, enhance carrier mobility and promote the fill factor of the device.